Entre ciência e pseudociência : análise do pensamento científico em estudantes universitários - Garcia, Paula Fernanda Martins (2021)
Science is a fundamental engine for driving knowledge and social progress construction. However, despite the growing prestige of science, pseudoscientific beliefs continue to be widespread and accepted. It was found that university students, for example, have high levels of pseudoscientific beliefs, although the role of universities is to produce and disseminate scientific knowledge. Therefore, it is necessary to understand the mechanisms that contribute to the propagation and acceptance of pseudoscience among those who have access to scientific method and scientific knowledge. Hence, two studies were carried out with 4,477 students from universities in 26 states in Brazil. Study 1 aimed to investigate pseudoscientific beliefs and science literacy in university students using two instruments, as follows: one instrument aimed to analyze pseudoscientific beliefs and the other, knowledge of the scientific method. Study 2 aimed to assess whether students' science literacy, as well as their beliefs in pseudosciences, are related to reports of preventive measures adopted by students during the COVID-19 pandemic. In the referred study, in addition to the two instruments used in Study 1, questions were added so that students could report which protective measures they adhered to during the pandemic period. Study 1 showed that the students obtained better results in the instrument that assessed knowledge of the scientific method (M=64.8) than in the instrument that assessed belief in pseudoscience (M=56.7). Thus, the students had high levels of pseudoscientific beliefs, contributing to the hypothesis raised by the literature that graduation, in traditional ways, may not significantly contribute to the reduction of these beliefs, despite providing knowledge about the scientific method. On the other hand, Study 2 showed that the students who checked the veracity of information about COVID-19 had better results in the assessment of knowledge of the scientific method (M=66.4) and were more able to identify and reject pseudoscientific claims (57.4) compared to the results achieved by the group that claimed not to check the veracity of the information sources, both in the assessment of knowledge of the scientific method (M=58.1) and in the rejection of pseudoscientific beliefs (M=53.8). Moreover, the students who reported practicing social distancing also had better average results regarding rejection of pseudoscience (M=57.2) and greater knowledge of the scientific method (M=65.7) than those who said that they did not respect social distancing (M= 51.8; M=56.5, respectively). Although the scientific knowledge of students apparently tends to increase during university education, there is still a great spread of pseudoscientific beliefs in this environment.